2017
DOI: 10.1038/s41598-017-03666-0
|View full text |Cite
|
Sign up to set email alerts
|

GABAA receptor subunit gene polymorphisms predict symptom-based and developmental deficits in Chinese Han children and adolescents with autistic spectrum disorders

Abstract: GABAA receptor subunit genes GABRB3, GABRA5, and GABRG3 located on chromosome 15q11-q13 have been implicated in the etiology of autistic spectrum disorders (ASD). This study intended to investigate the possible role of single-nucleotide polymorphisms (SNPs) present in GABRB3 (rs2081648 and rs1426217), GABRA5 (rs35586628), and GABRG3 (rs208129) genes in ASD susceptibility and symptom-based and developmental phenotypes of ASD in Chinese Han children and adolescents. 99 ASD patients and 231 age- and gender- frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Furthermore, polymorphisms [6470] and abnormal expression levels [7174] of several GABA A receptor subunit genes have also been identified in individuals with ASD. In fact, single-nucleotide polymorphisms in all three of the GABA A receptor genes that are duplicated in Dup15q syndrome were recently found to predict symptom-based and developmental deficits in a large ( n = 99) cohort of children and adolescents with ASD [75]. At the same time, EEG beta band anomalies have been linked to ASD [7679], though arguably less so than anomalies in other frequency bands [80].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, polymorphisms [6470] and abnormal expression levels [7174] of several GABA A receptor subunit genes have also been identified in individuals with ASD. In fact, single-nucleotide polymorphisms in all three of the GABA A receptor genes that are duplicated in Dup15q syndrome were recently found to predict symptom-based and developmental deficits in a large ( n = 99) cohort of children and adolescents with ASD [75]. At the same time, EEG beta band anomalies have been linked to ASD [7679], though arguably less so than anomalies in other frequency bands [80].…”
Section: Discussionmentioning
confidence: 99%
“…A still‐speculative theory proposes that the atypical distribution of GABAergic interneurons in autism explains their deficits in global perception and their insistence on sameness . Accordingly, a recent study showed that different subunits of the GABA A receptor are associated with specific autism symptoms such as deficits in social interactions, insistence on sameness, and language impairments . Being the main inhibitory neurotransmitter in the central nervous system, GABA is involved in the inhibition of wake‐promoting cellular populations in the brainstem, the hypothalamus, and the basal forebrain.…”
Section: Biological Factors Predisposing Sleep Problems In Children Wmentioning
confidence: 99%
“…46 Accordingly, a recent study showed that different subunits of the GABA A receptor are associated with specific autism symptoms such as deficits in social interactions, insistence on sameness, and language impairments. 47 Being the main inhibitory neurotransmitter in the central nervous system, GABA is involved in the inhibition of wake-promoting cellular populations in the brainstem, the hypothalamus, and the basal forebrain. GABA acts through GABA A , GABA B , and GABA C receptors, the first being the most well-known for its role in sleep initiation and maintenance.…”
Section: Biological Factors Predisposing Sleep Problems In Children Wmentioning
confidence: 99%
“…The list of predicted genes includes GABRA5 . It transcribes for the subunit 5 of GABA receptor alpha whose reduced expression and reduced protein level have been described in autism [44], and the SNPs of this gene are biomarkers of symptoms and developmental deficit in Han Chinese with autism [45]. The inclusion of this gene in the core list strengthens the evidences of imbalance between excitatory and inhibitory neurotransmission in ASDs and abnormalities in glutamate and GABA signaling as possible causative pathological mechanisms of ASDs.…”
Section: Discussionmentioning
confidence: 99%